Estimating optimal conservation in agricultural landscapes when costs and benefits of conservation measures are heterogeneous in space and over time - Frank Wätzold; Nele Lienhoop; Martin Drechsler; Josef Settele (UFZ-Umweltforschungszentrum Leipzig-Halle, 2006)
Designing agri-environmental schemes targeted at conservation poses the key question of how many financial resources should be allocated to address a particular aim such as the conservation of an endangered species. Economists can contribute to an answer by estimating the 'optimal level of species conservation'. This requires an assessment of the supply and the demand curve for conservation and a comparison of the two curves to identify the optimal conservation level. In a case study we estimate the optimal conservation level of Large Blue butterflies (protected by the EU Habitats Directive) in the region of Landau, Germany. The difference to other studies estimating optimal conservation is that a problem is addressed where costs and benefits of conservation measures are heterogeneous in space and over time. In our case study we find a corner solution where the highest proposed level of butterfly conservation is optimal. Although our results are specific to the area and species studied, the methodology is generally applicable to estimate how many financial resources should be allocated to conserve an endangered species in the context of agri-environmental schemes.
Keywords: 330; agri-environmental policy; biodiversity; optimal conservation; spatial heterogeneity; willingness-to-pay; Biodiversität; Naturschutz; Agrarsubvention; Willingness to pay; Kosten-Nutzen-Analyse; Deutschland